Predicting MIRA Patients’ Performance Using Virtual Rehabilitation Programme by Decision Tree Modelling - Zainal N.; Al-Hadi I.A.A.-Q.; Ghaleb S.M.; Hussain H.; Ismail W.; Aldailamy A.Y. (Springer, 2024)
Indexed by Scopus